Environmental and anthropogenic correlates of migratory speeds among Atlantic salmon smolts. (26th December 2020) - Harbicht, Andrew B.; Nilsson, P. Anders; Österling, Martin; Calles, Olle
Abstract: Dams, weirs, and hydropower facilities are often cited as migratory barriers which impart significant reductions in fitness among migratory fish species. Even where upstream and downstream passage options are available, barrier passage can still often result in energetic or physical costs which compound delays or cause mortality. Past studies have identified variables associated with such fitness reductions, though few examine their effects in the context of the whole river scale. To this end, we assessed the migratory rates and downstream passage of radio‐tagged Atlantic salmon ( Salmo salar ) smolts through nine river sections (including two reservoir sections and one dammed section) along a 20 km stretch of river. Migration stoppages were not found to be elevated in reservoir or dammed sections, while migration rates were best described by physical river properties (width), biological traits (smolt total length), and seasonal variables (diel period) rather than anthropogenic factors. These results suggest the negative effect of reservoirs may primarily be due to their influence on river width and may be negligible when width is largely unaffected by an impoundment. Similarly, spilling water during fish migrations as a mitigative measure appears to make delays negligible. These conditions and actions may not completely marginalize the effect of dams, however, as a negative trend was still observed resulting from passage effects at the dam.